Caroxylon camphorosma, a new combination for Salsola camphorosma (S. camphorosmoides Iljin, nom. illeg., non Desf.) (Chenopodiaceae) - Mosyakin, Sergei L. (Phytotaxa, 2019)
Recent molecular phylogenetic, morphological and anatomical studies (e.g., Akhani et al. 2007, Wen et al. 2010, Voznesenskaya et al. 2013, Schüssler et al. 2017) resulted in recognition of several monophyletic genera instead of the phylogenetically unnatural Salsola Linnaeus (1753: 222) sensu lato. In particular, the taxonomic resurrection of the genus Caroxylon Thunberg (1782: 37) prophetically proposed by Tzvelev (1993, see also Tzvelev 1996, 2012) was convincingly confirmed by molecular evidence (Akhani et al. 2007, Wen et al. 2010, Feodorova 2011, 2012, Feodorova & Samigullin 2014, Schüssler et al. 2017, and references therein); see also taxonomic and nomenclatural overviews and updates (e.g., Mosyakin et al. 2017, Mucina 2017). The taxonomic recognition of Caroxylon and other segregate genera resulted in numerous nomenclatural changes, in particular, transfers of taxa from Salsola sensu lato to other currently accepted genera (see e.g., Akhani et al. 2007, Feodorova 2011, 2015, Falatoury et al. 2017, Mucina 2017). However, it appears that not all currently recognized taxa originally described in Salsola have been properly transferred to Caroxylon. One interesting nomenclatural case is considered here.